Development of a mHealth Real-Time Pain Self-Management App for Adolescents With Cancer: An Iterative Usability Testing Study. (July 2017) - Jibb, Lindsay A.; Cafazzo, Joseph A.; Nathan, Paul C.; Seto, Emily; Stevens, Bonnie J.; Nguyen, Cynthia; Stinson, Jennifer N.
Purpose: A user-centered design approach was used to refine the mHealth Pain Squad + real-time pain self-management app for adolescents with cancer for its usability (defined as being easy to use, easy to understand, efficient to complete, and acceptable).Method: Three iterative usability testing cycles involving adolescent observation and interview were used to achieve this objective. During each cycle, adolescents used the app while "thinking aloud" about issues encountered. Observed difficulties and errors were recorded and a semistructured interview about the experience was conducted. Using a qualitative conventional content analysis approach, themes related to app usability were identified.Results: Participants required an average of 4.3 minutes to complete the pain assessment component of Pain Squad+ . Overall, the app was acceptable. Problematic issues related to software malfunction, interface design flaws, and confusing text. Software revisions were made to address each issue.Conclusion: The multifaceted usability approach used provided insight into how a real-time app can be made acceptable to adolescents with cancer and succeeded in developing a Pain Squad+ app that is fit for future effectiveness testing.